Standardized Arrabidaea chica Extract Shows Cytoprotective Effects in Zoledronic Acid-Treated Fibroblasts and Osteoblasts - Wiziack Zago PM; Oliveira Sousa IM; Servat-Medina L; Jorge MP; Lima Neto LG; Hass V; Li X; Tasca Gois Ruiz AL; Saxena D; Foglio MA (Dove Medical Press, 2020)
Patricia Maria Wiziack Zago,1 Ilza Maria Oliveira Sousa,2 Leila Servat-Medina,2 Michelle Pedroza Jorge,2 Lidio Gonçalves Lima Neto,3 Viviane Hass,4 Xin Li,5 Ana Lucia Tasca Gois Ruiz,2 Deepak Saxena,5 Mary Ann Foglio2 1Sao Leopoldo Mandic Medical School, Araras, São Paulo, Brazil; 2Faculty of Pharmaceutical Sciences at University of Campinas, Campinas, São Paulo, Brazil; 3Postgraduate Program in Parasitic Biology, CEUMA University, São Luis, Maranhão, Brazil; 4School of Dentistry, University of Missouri-Kansas City, Kansas City, MO, USA; 5College of Dentistry, New York University, New York, NY, USACorrespondence: Mary Ann FoglioFaculty of Pharmaceutical Sciences at University of Campinas, Rua Candido Portinari 200, CEP: 13083-871, Campinas, São Paulo, BrazilTel +55 19 3521-8132Email maryann.foglio@fcf.unicamp.brIntroduction: Osteonecrosis of the jaw is a condition associated with intraoral ulceration and bone necrosis induced by antiresorptive medications, such as zoledronic acid, a bisphosphonate. Previous data on Arrabidaea chica (H&B.) Verlot wound healing activity prompted the study reported herein on A. chica standardized hydro alcoholic extract in vitro cytoprotective activity data on epithelial and osteoblastic cells exposed to zoledronic acid (ZA).Methods: Primary human gingival fibroblasts and murine pre-osteoblasts were treated with ZA 10 μM together with 5 or 10 μg.mL− 1 A. chica extract for 24h and 48 h. At both times, cells were submitted to viability assay and caspase 3/7 activation evaluation. Statistical analysis used one-way ANOVA and p=0.05.Results: In cell viability assay, a drastic damage effect of ZA appeared after 48 h in both epithelial (55.8%) and pre-osteoblastic cells (39.7%). When treated with ZA in combination with A. chica extract, cells showed higher viability values: 74.1%– 82.3% for fibroblasts and 66% for pre-osteoblasts. Furthermore, the combined treatment presented lower caspase 3/7 activation in fibroblasts and pre-osteoblasts.Conclusion: At low concentrations, A. chica extract showed promising cytoprotective effects against ZA-induced damage actions; however, further in vitro and in vivo studies are required to establish the mechanism of action.Keywords: Arrabidaea chica, zoledronic acid, epithelial cells, osteoblasts, fibroblasts